Two-dimensional ZrO2-RuO2 composite supported catalysts, their preparation, and their application in the catalytic oxidation of HCl.
Patent Information
- Application Number
- CN202410034041.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-10
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-01-10
AI Technical Summary
但关于钌锆二维复合负载型催化剂在氯化氢氧化成氯气反应中未见报道
[0041]本发明提供了一种全新的负载型催化剂,其可基于成分、成分之间复合的二维结构以及晶面暴露等特点的联合,能够适配HCl催化氧化应用要求,可以意外地表现出优异的HCl催化氧化活性和稳定性。
Smart Images

Figure CN118122320B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalytic materials, specifically relating to the field of catalytic oxidation of HCl to produce chlorine. Technical Background
[0002] Chlorine (Cl2) is widely used in polymer chemicals, energy chemicals, and fine chemicals industries, including polyurethane, silicone, epoxy resin, chlorinated rubber, polysilicon manufacturing, disinfectants, food additives, and cosmetic auxiliaries. A significant limiting factor in chlorine use in most chlorine-consuming industries is the increasing amount of hydrogen chloride produced as a byproduct. Recycling hydrogen chloride to chlorine is a promising solution. Recent decades of development have shown that catalytic oxidation is the most effective solution, especially the Deacon reaction, which has the greatest industrial potential due to its simple operation and low equipment cost.
[0003] The Deacon reaction converts hydrogen chloride to chlorine gas in the presence of a catalyst. The type of catalyst directly affects the conversion rate of hydrogen chloride in the Deacon reaction. Currently, the catalysts used in the Deacon reaction mainly employ metallic elements such as chromium, copper, and ruthenium. Currently, commercially available catalysts are ruthenium catalysts supported on rutile TiO2 or SnO2. However, ruthenium catalysts still suffer from drawbacks such as activity reduction, volatilization, and sintering during long-term use. Therefore, the development of novel ruthenium catalysts remains of significant application value.
[0004] Sumitomo Chemical Co., Ltd., in patent CN1145328A, mentions using titanium tetrachloride and zirconium tetrachloride to prepare a mixed support for ruthenium, producing a powder catalyst, which is then shaped for use in a fixed bed. Bayer Materials Science AG, in patent CN200780018676, loads ruthenium onto SnO2, using ZrO2 as a binder. Hanwha Silosun Co., Ltd., in patent CN201980082064, mentions a composite of Al2O3, CeO2, and ZrO2, with ruthenium loaded on it, calcined at 300-400℃; patent CN202080085814 also attempts to shape the above support. Literature reports the use of RuO2-CeO2-ZrO2 in other oxidation reactions, such as wet oxidation, benzyl alcohol oxidation, and CO oxidation. However, there are no reports on the use of ruthenium-zirconium two-dimensional composite supported catalysts in the hydrogen chlorination to chlorine reaction. Summary of the Invention
[0005] To address the need for improved activity and stability of existing commercial ruthenium catalysts supported on rutile titanium dioxide or tin dioxide, the primary objective of this invention is to provide a two-dimensional ZrO2-RuO2 composite supported catalyst designed to improve the catalytic oxidation capacity and stability of HCl.
[0006] The second objective of this invention is to provide a method for preparing the two-dimensional ZrO2-RuO2 composite supported catalyst, with the aim of successfully preparing the catalyst.
[0007] The third objective of this invention is to provide the application of the aforementioned two-dimensional ZrO2-RuO2 composite supported catalyst in the catalytic oxidation of hydrogen chlorination to produce chlorine.
[0008] A two-dimensional ZrO2-RuO2 composite supported catalyst, comprising a support and the active component supported thereon;
[0009] The active ingredient is a ZrO2-RuO2 composite material with a two-dimensional nanostructure; and the RuO2 therein has a 110 dominant crystal plane.
[0010] This invention provides a novel supported catalyst in which the ZrO2-RuO2 composite exhibits a two-dimensional structure, with the RuO2 having a 110-fold predominantly exposed crystal facet. Research in this invention demonstrates that the unique components, morphology, and crystal facets of the material can achieve synergy, unexpectedly exhibiting excellent HCl catalytic oxidation activity and stability.
[0011] In this invention, there are no special requirements for the type of support, as long as it can meet the needs of the HCl catalytic oxidation field. For example, it may include at least one of alumina, silicon dioxide, titanium dioxide, cerium dioxide, and tin dioxide.
[0012] In this invention, the RuO2 has a 110-fold predominantly exposed crystal plane, and its texture factor can be above 20%, and more specifically, 20-90%.
[0013] In this invention, the loading amounts of ZrO2 and RuO2 in the two-dimensional ZrO2-RuO2 composite supported catalyst can be reasonably adjusted according to catalytic requirements. For example, the loading amount can be above 0.1 wt.%. Considering processing costs and economic efficiency, the loading amount of ZrO2 is preferably above 2 wt.%, further above 4 wt.%, even further above 5-15 wt.%, and even further above 8-10 wt.%.
[0014] The loading of RuO2 is preferably 0.5 wt.% or more, further 1 wt.% or more; even more 1 to 5 wt.%, further 1 to 3 wt.%, and even more 1 to 2 wt.%.
[0015] This invention also provides a method for preparing a two-dimensional ZrO2-RuO2 composite supported catalyst, the steps of which include:
[0016] Step (1):
[0017] The support and zirconium source are pre-composite and then subjected to a first-stage calcination to obtain ZrO2 intermediate A, wherein the temperature of the first-stage calcination is 500-1000℃;
[0018] Step (2):
[0019] The ZrO2-supported intermediate A and the ruthenium source were combined and then subjected to a second-stage calcination to obtain the RuO2-ZrO2-supported intermediate B. The temperature of the second-stage calcination was 200-350℃.
[0020] Step (3):
[0021] The two-dimensional ZrO2-RuO2 composite supported catalyst was prepared by third-stage calcination of RuO2-ZrO2 intermediate B under a protective atmosphere, wherein the temperature of the third-stage calcination was 350-550℃.
[0022] This invention demonstrates that successfully preparing the material requires addressing challenges such as the two-dimensionalization of ZrO2-RuO2 and the induced exposure of dominant crystal faces. To address these challenges, this invention innovatively provides a three-stage calcination approach: Zr followed by Ru. Furthermore, by jointly controlling the temperature during each of the three calcination stages, a synergistic effect is unexpectedly achieved, inducing the exposure of dominant crystal faces. Moreover, this approach promotes the two-dimensionalization of the active components, thereby exposing more reactive sites and improving the stability against HCl. Research indicates that the material prepared by this method unexpectedly and significantly improves the activity and stability of the catalytic oxidation of HCl to Cl2.
[0023] In this invention, the zirconium source can be a conventional Zr-containing raw material, such as an inorganic zirconium source and / or an organic zirconium source. Alternatively, the inorganic zirconium source may include at least one of zirconium nitrate, zirconium sulfate, zirconium chloride, and zirconium oxychloride.
[0024] In this invention, the support and zirconium source can be composited using known processes. As an example, the support and zirconium source can be composited using a liquid-phase impregnation method or a precipitation method.
[0025] The impregnation method, for example, involves immersing the carrier in a solution containing a zirconium source, followed by desolvation to obtain the desired composite.
[0026] In this invention, the atmosphere of the first calcination stage is an oxidizing atmosphere; preferably an oxygen-containing atmosphere, which includes oxygen, air, etc.; considering the processing cost, air is even more preferred.
[0027] Preferably, the temperature of the first calcination stage is 650–950°C, and more preferably 800–900°C;
[0028] In this invention, the calcination time in the first stage is more than 0.5 hours. Considering the preparation efficiency, it can be further extended to 1 to 10 hours, further extended to 2 to 5 hours, and further extended to 2 to 3 hours.
[0029] In this invention, the ruthenium source can be any raw material capable of providing Ru, such as inorganic ruthenium sources and / or organic ruthenium sources. Further, the inorganic ruthenium source includes, but is not limited to, at least one of ruthenium trichloride, ruthenium trichloride hydrate, ruthenium chloride, ruthenium chloride hydrate, and ruthenium amino complexes.
[0030] In this invention, the ZrO2-supported intermediate A and the ruthenium source can be obtained by compounding based on known processes, for example, by liquid phase impregnation or precipitation.
[0031] In this invention, the atmosphere of the second calcination stage is an oxidizing atmosphere; preferably an oxygen-containing atmosphere, which includes oxygen, air, etc., and preferably air.
[0032] Preferably, the temperature of the second calcination stage is 250–300°C, more preferably 250–270°C;
[0033] In this invention, the second calcination time is more than 1 hour. Considering the preparation efficiency, it can be further extended to 5 to 30 hours, and even further extended to 10 to 20 hours.
[0034] In this invention, a third calcination is performed after the first Zr calcination and the second Ru calcination process. This facilitates the control of the physicochemical characteristics of the system's composition, thereby synergistically imparting the two-dimensional structure and the degree of exposure of the dominant crystal faces, and thus improving its HCl catalytic oxidation activity and stability.
[0035] In this invention, the atmosphere of the third calcination stage includes at least one of nitrogen, argon, oxygen, air, and carbon dioxide.
[0036] Preferably, the temperature of the third calcination stage is 380–520°C, more preferably 400–500°C, and even more preferably 400–450°C;
[0037] Preferably, the calcination time in the third stage is 4 hours or more, further 4 to 120 hours, more preferably 8 to 80 hours, and even more preferably 55 to 75 hours.
[0038] The present invention also provides an application of the two-dimensional ZrO2-RuO2 composite supported catalyst described above, using it as a catalyst for the catalytic oxidation of HCl and oxygen to produce chlorine.
[0039] In this invention, the conditions for the catalytic oxidation reaction stage are not particularly required and can refer to the conventional Deacon reaction method and conditions. For example, the oxidation reaction temperature is 200–450°C; preferably 250–370°C. The molar ratio of HCl to oxygen is 1:0.25–4. More preferably, it can be 1:0.25–1.
[0040] Beneficial effects
[0041] This invention provides a novel supported catalyst that, based on the combination of characteristics such as components, the two-dimensional structure of composite components, and exposed crystal faces, can be adapted to the requirements of HCl catalytic oxidation applications and can unexpectedly exhibit excellent HCl catalytic oxidation activity and stability.
[0042] This invention innovatively provides a three-stage calcination approach using Zr followed by Ru, further enhanced by coordinated temperature control across the three calcination stages. This unexpectedly achieves synergy, inducing the exposure of dominant crystal faces. Furthermore, it promotes the two-dimensionalization of active components, thereby exposing more reactive sites and improving the stability against HCl. Studies have shown that the material prepared by this method unexpectedly and significantly improves the activity and stability of the catalytic oxidation of HCl to Cl2.
[0043] The catalyst described in this invention is particularly well-suited for the catalytic oxidation of hydrogen chloride. It exhibits excellent catalytic activity and stability; for example, the space-time yield of chlorine reaches 198 g. Cl2 ·g Ru -1 ·h -1 It has a stability of over 100 hours, balancing excellent catalytic activity and stability. Attached Figure Description
[0044] Appendix Figure 1 Example 1: Product of the catalyst before the third stage of calcination (i.e., product of the second stage of calcination).
[0045] Transmission electron microscope (TEM) image;
[0046] Appendix Figure 2 Example 1: Transmission electron microscope (TEM) image of the product (catalyst) after the third stage of catalyst calcination;
[0047] Appendix Figure 3 X-ray diffraction (XRD) patterns of the catalyst before and after 100 h of reaction in Example 1. Detailed Implementation
[0048] In the following examples, the room temperature is 5–45°C, and can be further defined as 20–30°C.
[0049] In the following examples, stable operation refers to the operating time under the stated spatiotemporal yield.
[0050] Example 1
[0051] Step (1): First stage of calcination
[0052] Weigh 0.105 g of commercially available ZrOCl2·8H2O and 0.4 g of 40-60 mesh granular active Al2O3, and dissolve them in a bottle containing 1 mL of water. Sonicate the bottle for 5 min, then let it stand at room temperature for 12 h, and then dry it overnight in an oven at 120 °C. Afterward, transfer it to a crucible and calcine it in a muffle furnace at 850 °C (labeled T1) for 3 h (labeled t1) to obtain the ZrO2-Al2O3-850 support.
[0053] Step (2): Second stage calcination
[0054] 0.15 g of ZrO2-Al2O3-850 support was mixed with 0.4 mL of RuCl3·xH2O (35%-42% Ru) aqueous solution (10 g / L) and dried overnight in an oven at 60 °C. The mixture was then transferred to a crucible and calcined in a muffle furnace at 260 °C (labeled T2) for 16 h (labeled t2) to obtain RuO2 / ZrO2-Al2O3-850.
[0055] Step (3): Third stage calcination
[0056] The catalyst was obtained by calcining it in a nitrogen gas stream (30 mL / min) at 400 °C (labeled as T3) for 72 h (labeled as t3), denoted as: RuO2 / ZrO2-Al2O3-850(72h). The mass fractions (loadings) of RuO2 and ZrO2 were 1.3% and 10%, respectively.
[0057] The catalyst performance was tested as follows: 0.1 g of RuO2 / ZrO2-Al2O3-850 (72 h) catalyst was weighed and placed in a fixed-bed quartz reaction tube. Nitrogen gas was introduced at a rate of 30 mL / min, and the catalyst bed was heated from room temperature to 300 °C at a rate of 5 °C / min. Then, hydrogen chloride gas was introduced at a rate of 32 mL / min and oxygen gas at a rate of 16 mL / min to carry out the reaction. Samples were taken at intervals, and the space-time yield of chlorine was calculated. The reaction products were collected with a low-concentration potassium iodide solution at room temperature, and their composition was determined by titration with a standard sodium thiosulfate solution. The test results showed that the space-time yield of chlorine on the RuO2 / ZrO2-Al2O3-850 (72 h) catalyst was 198 g. Cl2 ·g Ru -1 ·h -1 It can run stably for more than 100 hours.
[0058] Example 2
[0059] Compared with Example 1, the only difference is that the amount of ZrOCl2·8H2O and RuCl3·xH2O in the raw materials are changed so that the loading of ZrO2 in the catalyst is 8 wt.% and the loading of RuO2 is 2 wt.%. The other preparation steps are the same as in Example 1.
[0060] The obtained catalyst was subjected to the same loading, reaction, and performance testing methods as in Example 1. The catalyst's performance was measured as follows: a space-time yield of chlorine of 184 g. Cl2 ·g Ru -1 ·h -1 It can run stably for more than 100 hours.
[0061] Example 3
[0062] Compared with Example 1, the only difference is that ZrOCl2·8H2O in the raw materials is replaced with Zr(NO3)4·5H2O (the total loading of ZrO2 in the catalyst is the same as in Example 1), while the other preparation steps are the same as in Example 1. The obtained catalyst was subjected to sample loading, reaction, and performance testing using the method of Example 1. The measured performance of the catalyst was: a space-time yield of chlorine of 192 g. Cl2 ·g Ru -1 ·h -1 It can run stably for more than 100 hours.
[0063] Example 4
[0064] Compared to Example 1, the only difference is that the first calcination temperature T1 was changed to 950℃, and t1 was 2 hours; all other preparation steps remained the same as in Example 1. The resulting catalyst was subjected to the same loading, reaction, and performance testing methods as in Example 1. The catalyst performance was measured as follows: a space-time yield of chlorine of 176 g. Cl2 ·g Ru -1 ·h -1 It can run stably for more than 100 hours.
[0065] Example 5
[0066] Compared to Example 1, the only difference is that the second calcination temperature T2 was changed to 300℃ and t2 was 14h; all other preparation steps remained the same as in Example 1. The resulting catalyst was subjected to the same loading, reaction, and performance testing methods as in Example 1. The catalyst performance was measured as follows: a space-time yield of chlorine of 158g. Cl2 ·g Ru -1 ·h -1It can run stably for more than 100 hours.
[0067] Example 6
[0068] Compared to Example 1, the only difference is that the third-stage calcination temperature T3 is changed to 500℃ and t3 is 60h; other preparation steps remain the same as in Example 1. The resulting catalyst was subjected to sample loading, reaction, and performance testing using the method described in Example 1. The catalyst performance was measured to be: a space-time yield of chlorine reaching 189%.
[0069] g Cl2 ·g Ru -1 ·h -1 It can run stably for more than 100 hours.
[0070] Example 7
[0071] Compared to Example 1, the only difference is that the third calcination time t3 is changed to 120 h; all other preparation steps remain the same as in Example 1. The resulting catalyst was subjected to the same loading, reaction, and performance testing methods as in Example 1. The catalyst performance was measured as follows: space-time yield of chlorine 135 g. Cl2 ·g Ru -1 ·h -1 .
[0072] Example 8
[0073] Compared to Example 1, the only difference is that the alumina support is replaced with silica; all other preparation steps remain the same as in Example 1. The resulting catalyst was subjected to the same loading, reaction, and performance testing methods as in Example 1. The catalyst performance was measured to be: a space-time yield of chlorine reaching 175 g. Cl2 ·g Ru -1 ·h -1 It can run stably for more than 100 hours.
[0074] Comparative Example 1
[0075] The raw material ZrOCl2·8H2O in Example 1 was removed, while the other preparation steps remained the same as in Example 1. The resulting catalyst was subjected to sample loading, reaction, and performance testing using the method described in Example 1. The catalyst performance was measured to be: space-time yield of chlorine 129 g. Cl2 ·g Ru -1 ·h -1 .
[0076] Comparative Example 2
[0077] The raw material Al2O3 in Example 1 was removed, while the other preparation steps remained the same as in Example 1. Only a powder product could be obtained; a molded catalyst product could not be directly obtained.
[0078] Comparative Example 3
[0079] The first calcination temperature T1 in Example 1 was changed to 450℃, while other preparation steps remained the same as in Example 1. The resulting catalyst was subjected to sample loading, reaction, and performance testing using the method described in Example 1. The catalyst performance was measured to be: a space-time yield of chlorine of 99 g. Cl2 ·g Ru -1 ·h -1 .
[0080] Comparative Example 4
[0081] The second calcination temperature T2 in Example 1 was changed to 400℃, while other preparation steps remained the same as in Example 1. The resulting catalyst was subjected to sample loading, reaction, and performance testing using the method described in Example 1. The catalyst performance was measured to be: space-time yield of chlorine 79 g. Cl2 ·g Ru -1 ·h -1 .
[0082] Comparative Example 5
[0083] The third calcination temperature T3 in Example 1 was changed to 600℃, while other preparation steps remained the same as in Example 1. The resulting catalyst was subjected to sample loading, reaction, and performance testing using the method described in Example 1. The catalyst performance was measured to be: a space-time yield of chlorine of 83 g. Cl2 ·g Ru -1 ·h -1 .
[0084] Comparative Example 6
[0085] The calcination atmosphere in step (3) of Example 1 was changed to hydrogen, while the other preparation steps remained the same as in Example 1. The resulting catalyst was subjected to sample loading, reaction, and performance testing using the method described in Example 1. The catalyst performance was measured to be: space-time yield of chlorine 107 g. Cl2 ·g Ru -1 ·h -1 .
[0086] Comparative Example 7
[0087] Compared with Example 1, the only difference is that after Zr and Ru are combined in one pot, they are sintered in three stages. The difference is that ZrOCl2·8H2O and RuCl3·xH2O are dissolved together in water, granular active Al2O3 is added, and ultrasonication is performed for 5 minutes. Then, it is left to stand at room temperature for 12 hours and then placed in an oven at 120°C overnight to dry.
[0088] The first stage of calcination was then carried out under conditions T1 and t1, followed by the second stage under conditions T2 and t2, and finally the third stage under conditions T3 and t3; all other operations and parameters were the same as in Example 1.
[0089] The obtained catalyst was subjected to the same loading, reaction, and performance testing methods as in Example 1. The catalyst performance was measured to be: space-time yield of chlorine gas 59 g. Cl2 ·g Ru -1 ·h -1 .
[0090] Comparative Example 8
[0091] Step (3) in Example 1 is removed, and the material prepared in step 2 is used directly as the catalyst.
[0092] The obtained catalyst was subjected to the same loading, reaction, and performance testing methods as in Example 1. The catalyst performance was measured to be: space-time yield of chlorine 106 g. Cl2 ·g Ru -1 ·h -1 .
[0093] Comparative Example 9
[0094] Compared to Example 1, the only difference is that the loading of Zr and Ru and the corresponding calcination sequence are changed; that is, the processing sequence is modified to steps 2, 1, and 3, specifically:
[0095] Al2O3 and RuCl3·xH2O were first combined and subjected to a first-stage loading calcination at T2 and t2 under the conditions of step 2. Then, the product of the first-stage calcination was used as a carrier and combined with ZrOCl2·8H2O under the conditions of step (1) and subjected to a second calcination at T1 and t1, followed by the treatment in step (3). The amount of components and other operating conditions were the same as in Example 1.
[0096] The obtained catalyst was subjected to the same loading, reaction, and performance testing methods as in Example 1. The catalyst performance was measured as follows: space-time yield of chlorine gas 35g. Cl2 ·g Ru -1 ·h -1 .
[0097] Comparative Example 10
[0098] In Example 1, ZrOCl2·8H2O was replaced with CeCl3 to prepare a catalyst with CeO2 replacing ZrO2 (the loading of CeO2 on the catalyst remained at 10% wt). Other preparation steps were consistent with Example 1. The resulting catalyst was subjected to sample loading, reaction, and performance testing using the method described in Example 1. The catalyst performance was measured as follows: space-time yield of chlorine gas 79 g. Cl2 ·g Ru -1 ·h -1 .
[0099] As can be seen from Examples 1-3, different zirconium sources, such as zirconium nitrate and zirconium oxychloride, have little effect on catalyst performance.
[0100] As can be seen from Example 1 and Comparative Example 1, the presence of ZrO2 is very important and has a significant impact on catalyst performance.
[0101] As can be seen from Example 1 and Comparative Example 2, the support is also very important for the catalyst. Without the addition of a support, a shaped catalyst product cannot be obtained directly.
[0102] As can be seen from Examples 1, 4-6, and Comparative Examples 3-5, under the preferred temperature, it can be combined with other process parameters to achieve excellent synergistic catalytic activity.
[0103] As can be seen from Examples 1 and 6, the atmosphere of the third calcination also has a significant impact on the catalyst performance. Nitrogen gas yields good catalyst performance. Other gases, such as hydrogen, do not promote catalyst performance.
[0104] As can be seen from Examples 1 and 7, the staged loading and calcination processes have a significant impact on catalyst performance. Secondary loading and calcination can yield better catalyst performance. One-pot calcination is detrimental to catalyst performance.
[0105] As can be seen from Example 1 and Comparative Example 8, the third calcination process has a significant impact on the performance of the catalyst. Eliminating the third calcination process is detrimental to the catalyst's performance.
[0106] As can be seen from Example 1 and Comparative Example 9, the loading order has a significant impact on the performance of the catalyst. Changing the loading order leads to a sharp decline in the performance of the catalyst.
[0107] As can be seen from Example 1 and Comparative Example 10, ZrO2 has irreplaceable uniqueness compared to other oxides such as CeO2, which is conducive to the full utilization of catalyst performance.
[0108] In summary, this invention innovatively loads ZrO2 and RuO2 onto the surface of a support under specific conditions, and then subjectes them to calcination under specific conditions. Through the combined control of three process conditions, including the ruthenium-zirconium ratio, calcination temperature and time during the two loading stages, and the combined control of the atmosphere, temperature and time during the third calcination, a highly active two-dimensional ZrO2-RuO2 composite supported catalyst is unexpectedly obtained. This is the key to this invention. In particular, it was found that through the third calcination treatment, the catalyst structure underwent three major changes that are beneficial to catalytic performance: (1) ZrO2 and RuO2 spread from three-dimensional nanoparticles into two-dimensional nanostructures, increasing the dispersion of the active components; (2) the recognized active crystal facet RuO2 (110) is more exposed; and (3) the lattice parameters of RuO2 are adjusted. It should be noted that the changes in the catalyst structure caused by the third calcination in this invention are different from the traditional preparation process of ruthenium-zirconium solid solutions. Rather, the changes are in morphology, crystal facets, and lattice parameters, which makes it exhibit better activity than the catalyst before calcination. See Appendix for details. Figure 1 Appendix Figure 2 Additionally, a comparison of the XRD patterns of the catalyst before and after 100 hours of reaction is attached. Figure 3 It can be seen that the crystal phase of the catalyst did not change before and after 100 hours of reaction, reflecting the stability of the catalyst structure of this invention.
[0109] In summary, the preparation process of the catalyst of the present invention is the result of coordinated control of multiple steps and factors. Neglecting certain steps or improper use of certain factors will not result in the successful acquisition of the catalyst of the present invention.
Claims
1. A two-dimensional ZrO2-RuO2 composite supported catalyst for catalytic oxidation of HCl and oxygen to produce chlorine, characterized in that, This includes the carrier and the active ingredient it carries; The active ingredient is a ZrO2-RuO2 composite material with a two-dimensional nanostructure; and the RuO2 therein has a 110 dominant crystal plane; The preparation steps of the two-dimensional ZrO2-RuO2 composite supported catalyst include: Step (1): The support and zirconium source are pre-composite and then subjected to a first-stage calcination to obtain ZrO2 intermediate A, wherein the temperature of the first-stage calcination is 500~1000℃; Step (2): The ZrO2-supported intermediate A and the ruthenium source were combined and then subjected to a second-stage calcination to obtain the RuO2-ZrO2-supported intermediate B. The temperature of the second-stage calcination was 200~350℃. Step (3): The two-dimensional ZrO2-RuO2 composite supported catalyst was prepared by calcining the RuO2-ZrO2 intermediate B in a protective atmosphere for a third stage, wherein the temperature of the third stage calcination was 350~550℃. The atmosphere of the third calcination stage includes at least one of nitrogen and argon.
2. The two-dimensional ZrO2-RuO2 composite supported catalyst as described in claim 1, characterized in that, The carrier includes at least one of alumina, silicon dioxide, titanium dioxide, cerium dioxide, and tin dioxide.
3. The two-dimensional ZrO2-RuO2 composite supported catalyst as described in claim 2, characterized in that, The texture factor of the 110 crystal plane of the RuO2 is above 20%.
4. The two-dimensional ZrO2-RuO2 composite supported catalyst as described in claim 3, characterized in that, The texture factor of the 110 crystal plane of the RuO2 is 20~90%.
5. The two-dimensional ZrO2-RuO2 composite supported catalyst according to any one of claims 1 to 4, characterized in that, In the two-dimensional ZrO2-RuO2 composite supported catalyst, the loading of ZrO2 and RuO2 is above 0.1 wt.%.
6. The two-dimensional ZrO2-RuO2 composite supported catalyst as described in claim 5, characterized in that, In the two-dimensional ZrO2-RuO2 composite supported catalyst, the loading of ZrO2 is above 2 wt.%; The RuO2 loading is above 0.5 wt.%.
7. The two-dimensional ZrO2-RuO2 composite supported catalyst as described in claim 6, characterized in that, In the two-dimensional ZrO2-RuO2 composite supported catalyst, the loading of ZrO2 is above 4 wt.%; The RuO2 loading is above 1 wt.%.
8. The two-dimensional ZrO2-RuO2 composite supported catalyst as described in claim 7, characterized in that, In the two-dimensional ZrO2-RuO2 composite supported catalyst, the loading of ZrO2 is 5~15 wt.%.
9. The two-dimensional ZrO2-RuO2 composite supported catalyst as described in claim 8, characterized in that, In the two-dimensional ZrO2-RuO2 composite supported catalyst, the loading of ZrO2 is 8~10 wt.%.
10. A method for preparing a two-dimensional ZrO2-RuO2 composite supported catalyst according to any one of claims 1 to 9, characterized in that the step include: Step (1): The support and zirconium source are pre-composite and then subjected to a first-stage calcination to obtain ZrO2 intermediate A, wherein the temperature of the first-stage calcination is 500~1000℃; Step (2): The ZrO2-supported intermediate A and the ruthenium source were combined and then subjected to a second-stage calcination to obtain the RuO2-ZrO2-supported intermediate B. The temperature of the second-stage calcination was 200~350℃. Step (3): The two-dimensional ZrO2-RuO2 composite supported catalyst was prepared by calcining the RuO2-ZrO2 intermediate B in a protective atmosphere for a third stage, wherein the temperature of the third stage calcination was 350~550℃. The atmosphere of the third calcination stage includes at least one of nitrogen and argon.
11. The preparation method according to claim 10, characterized in that, The zirconium source includes inorganic zirconium sources and / or organic zirconium sources.
12. The preparation method according to claim 11, characterized in that, The inorganic zirconium source includes at least one of zirconium nitrate, zirconium sulfate, zirconium chloride, and zirconium oxychloride.
13. The preparation method according to claim 10, characterized in that, The carrier and zirconium source are composited using liquid-phase impregnation or precipitation methods.
14. The preparation method according to claim 10, characterized in that, The atmosphere during the first calcination stage is an oxidizing atmosphere.
15. The preparation method according to claim 14, characterized in that, The atmosphere in the first calcination stage is an oxygen-containing atmosphere, which includes oxygen and selectively includes at least one of nitrogen and inert gases.
16. The preparation method according to claim 15, characterized in that, The atmosphere during the first calcination stage is air.
17. The preparation method according to claim 10, characterized in that, The temperature for the first stage of calcination is 650~950℃.
18. The preparation method according to claim 17, characterized in that, The temperature for the first stage of calcination is 800~900℃.
19. The preparation method according to claim 10, characterized in that, The first stage of calcination should last for more than 0.5 hours.
20. The preparation method according to claim 19, characterized in that, The first stage of calcination takes 1 to 10 hours.
21. The preparation method according to claim 20, characterized in that, The first stage of calcination takes 2 to 5 hours.
22. The preparation method according to claim 10, characterized in that, The ruthenium source includes inorganic ruthenium sources and / or organic ruthenium sources.
23. The preparation method according to claim 22, characterized in that, The inorganic ruthenium source includes at least one of ruthenium trichloride, ruthenium trichloride hydrate, ruthenium chloride, ruthenium chloride hydrate, and ruthenium ammonia complex.
24. The preparation method according to claim 22, characterized in that, The ZrO2-supported intermediate A and the ruthenium source are combined by liquid-phase impregnation or precipitation.
25. The preparation method according to claim 10, characterized in that, The atmosphere during the second calcination stage is an oxidizing atmosphere.
26. The preparation method according to claim 25, characterized in that, The atmosphere in the second calcination stage is an oxygen-containing atmosphere, which includes oxygen and selectively includes at least one of nitrogen and inert gases.
27. The preparation method according to claim 26, characterized in that, The atmosphere during the second calcination stage is air.
28. The preparation method according to claim 10, characterized in that, The temperature for the second stage of calcination is 250~300℃.
29. The preparation method according to claim 28, characterized in that, The temperature for the second stage of calcination is 250~270℃.
30. The preparation method according to claim 10, characterized in that, The second stage of calcination takes more than 1 hour.
31. The preparation method according to claim 30, characterized in that, The second calcination period is 5 to 30 hours.
32. The preparation method according to claim 10, characterized in that, The temperature of the third calcination stage is 380~520℃.
33. The preparation method according to claim 32, characterized in that, The temperature of the third calcination stage is 400~500℃.
34. The preparation method according to claim 33, characterized in that, The temperature of the third calcination stage is 400~450℃.
35. The preparation method according to claim 10, characterized in that, The third stage of calcination takes more than 4 hours.
36. The preparation method according to claim 35, characterized in that, The third calcination period is 4 to 120 hours.
37. The preparation method according to claim 36, characterized in that, The third calcination period is 8-80 hours.
38. The application of a two-dimensional ZrO2-RuO2 composite supported catalyst according to any one of claims 1 to 9 or a two-dimensional ZrO2-RuO2 composite supported catalyst prepared by the preparation method according to any one of claims 10 to 37, characterized in that, It was used as a catalyst in the reaction of HCl and oxygen oxidation to produce chlorine.
39. The application as described in claim 38, characterized in that, The temperature during the oxidation reaction stage is 200–450℃.
40. The application as described in claim 39, characterized in that, The temperature during the oxidation reaction stage is 250–370℃.
41. The application as described in any one of claims 38 to 40, characterized in that, The molar ratio of HCl to oxygen is 1:0.25~4.
Citation Information
Patent Citations
Method for producing chlorine by gas phase oxidation
CN101448572A
Catalyst for hydrogen chloride oxidation reaction for producing chlorine and preparation method thereof
CN113164924B
Molding catalyst for oxidation reaction of hydrogen chloride and preparation method thereof
CN114786807A
Catalyst for preparing chlorine by oxidizing hydrogen chloride, preparation method and applications thereof
CN111013580A
KR20220109106A